Evaluation of fungicides as seedling treatment for controlling Bakanae/Foot-rot (Fusarium moniliforme) disease in Basmati rice - VINEET K. SHARMA, PARAMJIT S. BAGGA* and (Indian Phytopathology, 2006)
Bakanae/Foot-rot (F. moniliforme, Sheldon) disease of Basmati rice causes significant reductions in grain yield and seed quality and may be associated with mycotoxin contamination of grain. The objective of this study was to evaluate fungicides, as seedling treatment, for controlling foot-rot disease, under natural infection and after artificial inoculation in the field. Five fungicides (Bavistin, Benomyl, Topsin-M, Tilt and Emisan) were applied to Basmati rice seedlings, before natural infection and after artificial inoculation, and transplanted in field. Foot-rot incidence was rated after 3 and 6 weeks of transplanting. The fungicides tested significantly reduced foot-rot incidence and improved grain yield. Seedling treatment with Bavistin or Benomyl @ 0.1% each for 6 and 8 h, respectively, were very effective. Seedling treatment for 1 h was ineffective and the fungicide efficacy increased as the duration of treatment increased to 6-8 hrs. Tilt 25 EC @ 0.05% was the most effective treatment in controlling foot-rot, but it showed signs of phytotoxicity and reduced plant height and grain yield under natural field infection. Although seed treatments are known to control Bakanae, this is the first report of fungicides, used as seedling treatment, for foot rot control. Prospects for chemical control of foot-rot infection in the field, after transplanting, by seedling treatment with fungicides, are bright.